2020
DOI: 10.1155/2020/4219180
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Particle Predictors of Arterial Stiffness after 17 Years of Follow Up: The Malmö Diet and Cancer Study

Abstract: Background. Central arterial stiffness is a surrogate of cardiovascular risk and predicts cardiovascular mortality. Apolipoprotein B lipoproteins are also established cardiovascular risk factors. It is not known whether specific lipoprotein subclasses measured in the Malmö Diet and Cancer Study and previously shown to be associated with coronary heart disease also predict arterial stiffening after a mean period of 17 years. Methods. Lipoprotein particle analysis was performed on 2,505 men and women from Malmö,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As TG contents are gradually degraded by lipoprotein lipase in the bloodstream, the cholesterol in RLP-C could also be involved in atherosclerosis plaque formation and subsequent cardiovascular events, and it has been recognized as more atherogenic and proinflammatory than the cholesterol in LDL-C [ 48 52 ]. A recent study indicated associations of plasma TGs and relatively small-sized LDL particles with the carotid-femoral PWV, despite no significant associations between VLDL/large IDL subclasses (the main carriers of TG in the blood) and the carotid-femoral PWV [ 53 ]. This raises the possibility that the TG content in TRLs may indirectly influence this process, considering greater small dense LDL generation in the presence of high VLDL-TG levels [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…As TG contents are gradually degraded by lipoprotein lipase in the bloodstream, the cholesterol in RLP-C could also be involved in atherosclerosis plaque formation and subsequent cardiovascular events, and it has been recognized as more atherogenic and proinflammatory than the cholesterol in LDL-C [ 48 52 ]. A recent study indicated associations of plasma TGs and relatively small-sized LDL particles with the carotid-femoral PWV, despite no significant associations between VLDL/large IDL subclasses (the main carriers of TG in the blood) and the carotid-femoral PWV [ 53 ]. This raises the possibility that the TG content in TRLs may indirectly influence this process, considering greater small dense LDL generation in the presence of high VLDL-TG levels [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Malmo Diet and Cancer study assessed the relationship between lipids and arterial stiffness on a cohort of 2505 patients during a median follow-up period of 17 years. It was indicated that TGs and HDL values predict carotid-femoral pulse wave velocity, whereas LDL does not [ 55 ].…”
Section: An Insight Into Other Implications Of Hypertriglyceridemia Beyond Atherosclerosismentioning
confidence: 99%
“…Abnormal lipid metabolism plays a key role in arteriosclerosis and atherosclerosis [ 9 12 ]. Lowering low-density lipoprotein cholesterol (LDL-C) primarily through statin is the leading therapy target for primary and secondary prevention of arteriosclerosis and atherosclerosis-related diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%